INTERPRETASI EKOWISATA OLEH PEMANDU WISATA DI KAWASAN PARIWISATA UBUD - Ashira Istighfarah; Anak Agung Gde Dalem; I Ketut Ginantra (SIMBIOSIS, 2024)
Tourism is one sector whose development which very intensively developed by the government. One form of sustainable tourism is ecotourism. Tour guides in ecotourism activities have an important role in connecting tourists with interpreted tourist attractions. Interpretation is a tool for connecting what tourists should get in an environment with what should be displayed. Interpretation is very important in educating tourists so they understand, respect, and support nature conservation, as well as provide satisfaction to tourists. Therefore, research on the interpretation of ecotourism is very important for tourism in the Ubud tourism resort. This research was conducted from January 17- May 3, 2023. The objective of this study is to determine the type of interpretation, the means of interpretation and the quality of the interpretation of tour guides. The methods used were observation, interviews, and questionnaires distribution. The interviewed guides were 16 informants and 30 tourists as respondents. This research found that there were 8 types of interpretation utilised by tour guides in the Ubud tourism resort: guided tour, point duty, roving interpretation, presentation, demonstrations, living history, interactive, and lecture or talk. There are 8 types of facilities used by guides in the Ubud tourism resort, print, self-guiding program signs, interpretive panels, visitor center, video, slideshow, observation hides, and handphone. The interpretation quality of the tour guides in the Ubud tourism resort was very good with a score of 92.21 %. Tourist satisfaction with the tour guide and the interpretation given by the tour guide was very good with a score of 85.16%. Keywords: Attractiveness, Bali, Tourist Destinations, Tourists, Villages